2007
DOI: 10.1111/j.1442-200x.2007.02460.x
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cell histiocytosis manifesting as recurrent simultaneous bilateral spontaneous pneumothorax in early infancy

Abstract: Langerhans cell histiocytosis (LCH) is a rare disorder characterized by infiltration of either single or multiple organs by a distinct cell type that is S-100 and CD1a positive and contains ultrastructural Birbeck granules on electron microscopy. Historically, LCH included four main clinical forms: Letter-Siwe disease, Hand-Schuller-Christian disease, eosinophilic granuloma (together grouped as histiocytosis) and Hashimoto-Pritzker disease. The writing group of the Histiocytotic Society in 1987 proposed the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Exceptionally, within children, even at a young age, LCH may present as severe lung damage, as typically observed in young adults. Management of these exceptional cases of young children with very severe lung disease is challenging; only few case reports have been published [7,[18][19][20][21][22][23][24][25][26][27]. Certain described children required management in an intensive care unit (ICU) for respiratory decompensation.…”
Section: Introductionmentioning
confidence: 99%
“…Exceptionally, within children, even at a young age, LCH may present as severe lung damage, as typically observed in young adults. Management of these exceptional cases of young children with very severe lung disease is challenging; only few case reports have been published [7,[18][19][20][21][22][23][24][25][26][27]. Certain described children required management in an intensive care unit (ICU) for respiratory decompensation.…”
Section: Introductionmentioning
confidence: 99%
“…3 In a small number of pediatric studies, SBSP was found to be associated with a few underlying lung diseases such as Langerhans cell histiocytosis (LCH). 4 The present study first reported the concurrence of these rare conditions, as a patient presenting a SBSP was diagnosed with of type 2 CPAM based on the typical radiological findings.…”
Section: Introductionmentioning
confidence: 76%
“…In another case, report published from Iran LCH was reported in a two-month-old infant with simultaneous bilateral and spontaneous pneumothorax. Due to destructive changes in in lungs, pneumothorax could happen in 10% of LCH cases with respiratory involvement [17]. In 2005, Nakhla et al reported a previously healthy 16 years old girl with sudden death.…”
Section: Discussionmentioning
confidence: 99%